The effect of nozzle shapes on the compactness and strength of structures printed by additive manufacturing of concrete - Lao, Wenxin (2018)
In direct-extrusion based Additive Manufacturing of Concrete (AMoC), the compactness and the mechanical strength of printed parts can be improved by optimizing the shape of extrudate. The shape of extrudate is significantly affected by the shape of nozzle outlet because of the viscoelastic behavior of fresh concrete. In this paper, different shapes of nozzle were tested to find the nozzle design for the optimized printing quality. Three different nozzles were fabricated by Fused Deposition Method mounted on a mechatronic nozzle, which was plugged on a robotic arm. From the compression test of the specimen and the observation of cross-section of the specimen, the mechanical strength and compactness of the sample were obtained. The result could help to find the relationship between the quality of concrete printing and the shape of nozzle outlet.